Anxiety disorders - a common problem about which we still don’t know enough - Giżewska, Kamila; Lorenc, Karol; Bielawska, Olga; Łoś, Tomasz; Kuc, Michał; Rogala, Maciej; Jabłońska, Klaudia; Gulbicka, Marta (Journal of Education, Health and Sport, 2023)
Anxiety disorders are the most common mental disorders. Up to one-third of the population suffers from them during their lifetime. An important problem is also the lack of awareness of patients about their disease. Only half of the anxiety disorders are diagnosed. Only a fifth of people suffering from anxiety disorders sought help from a specialist doctor. Only a third of patients are offered pharmacological treatment. The main symptom of this disease is an increased and intense feeling of anxiety. It is also associated with many other physical symptoms. It is correlative with a reduced quality of life and functioning in society. Diagnosis of anxiety disorders is very difficult due to the lack of specific imaging and laboratory tests that may be helpful in making or suggest a diagnosis. There is also a correlation between these disorders and the occurrence of depressive disorders, which is why the problem is complex and requires increased diagnostic sensitivity. Worldwide, anxiety disorders are underdiagnosed and undertreated, that’s why it’s so important to be aware of this disease entity. Prompt intervention by a physician is very important due to the increased frequency of suicides. The basic treatment is medication therapy with drugs from the SSRI and SNRI group combined with cognitive-behavioral therapy. Quick diagnosis and implementation of treatment contributes to a significant improvement in the quality of life of patients.